Prediction of Alzheimer's disease biomarker status defined by the ‘ATN Framework’ among cognitively healthy individuals: Results from the EPAD longitudinal cohort study - Calvin, C; Calvin, C; de Boer, C; Raymont, V; Gallacher, J; Koychev, I; The European Prevention of Alzheimer’s Dementia (EPAD) Consortium (BMC, 2020)
Background: The Amyloid/Tau/Neurodegeneration (ATN) framework has been proposed as a means of evidencing the biological state of Alzheimer’s disease (AD). Predicting ATN status in pre-dementia individuals therefore provides an important opportunity for targeted recruitment into AD interventional studies. We investigated the extent to which ATN-defined biomarker status can be predicted by known AD risk factors as well as vascular-related composite risk scores.